2019
DOI: 10.1111/vcp.12732
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of intraoperative impression smear cytology of intracranial granular cell tumors: Three cases

Abstract: Dog 1, a 14-year-old male neutered Shih Tzu, was presented with a 6-month history of seizures. Abnormal findings on the neurologic examination included confused mentation, nonambulatory tetraparesis, right torticollis, absent menace, reduced vestibuloocular reflex, and spontaneous vertical jerk nystagmus in both eyes (OU). The patient also had left-sided facial weakness and left-sided hemi-inattention. Postural reactions were absent in all limbs. A neuroanatomic localization was assigned to the right prosencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…This group also found that the microenvironment affects the morphology of the neoplastic GCT cells 4 . The cells contain abundant lysosomes, giving them a “granular” appearance 1‐5 . Oncocytomas originate from the duct of the glandular epithelium, usually in the oral cavity, salivary glands, or pharynx 1‐3 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This group also found that the microenvironment affects the morphology of the neoplastic GCT cells 4 . The cells contain abundant lysosomes, giving them a “granular” appearance 1‐5 . Oncocytomas originate from the duct of the glandular epithelium, usually in the oral cavity, salivary glands, or pharynx 1‐3 .…”
Section: Discussionmentioning
confidence: 99%
“…GCTs are most frequently found in the oral cavity of dogs and cats 1‐5 but can also be found in locations such as the brain, heart, lung, nerve roots, trachea, skin, and lymph nodes, 1,2 and eyelid 3 . GCT histogenesis is uncertain and might depend on the anatomic location of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations